Sastra dan Lingkungan: Fakta dan Relasi Ekologis dalam Kumpulan Cerpen Negeri Asap - Yulantomo, Aris; Nelfita, Yulia; Hidayat, Rian; Maprasit, Lateefah (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2025)
This study, titled “Literature and Environment: Ecological Facts and Relationships in the Short Story Collection Negeri Asap,” aims to examine (1) environmental issues, (2) narrative facts, and (3) the relationship between humans and nature in the short story collection Negeri Asap, using an ecocritical approach. The method employed is a descriptive narrative method. Data were collected through literature review and note-taking techniques. Of the seventeen short stories in the collection, four were selected as objects of analysis: Rumah di Ujung Kampung, Hantu Penunggu Pohon, Gadis Penunggu Hujan, and Keluh Kesah. This study identified a total of 66 data points, consisting of 9 data related to environmental issues, 51 narrative facts, and 6 data on human-nature relationships. The findings are as follows. First, the environmental issues identified include illegal logging, air pollution, forest fires, flooding, ozone layer depletion, and land conversion-driven displacement. Second, the narrative facts in the stories are categorized into three main elements: character, plot, and setting. The characters play a vital role in voicing environmental concerns and presenting various perspectives on environmental degradation. Third, the human-nature relationship is portrayed in two forms: a mutually dependent relationship and a disharmonious one caused by environmental exploitation. Through emotionally engaging narratives, the author conveys criticism of human actions that harm the environment and emphasizes the importance of environmental preservation to maintain ecosystem balance. Based on the results, the study concludes that short stories can serve as an effective medium for social reflection, raising public awareness of environmental issues and encouraging behavioral change for a more sustainable future.